Pengaruh kualitas produk dan kinerja karyawan terhadap kepuasan nasabah pada PT. Permodalan Nasional Madani Cabang Sindang Jaya - Nurmala; Rika Nurhidayah; Nur Azis (Universitas Tangerang Raya, 2023)
This research was conducted in order to gain an understanding of the influence of product quality and employee performance on Customer Satisfaction at PT. Madani National Capital Sindang Jaya Branch, Tangerang Regency. This research uses quantitative research methods. In this research, it includes Product Quality (X1) and Employee Performance (X2), Customer Satisfaction (Y). Research object PT. Madani National Capital Sindang Jaya Branch in Tangerang Regency. Simultaneous test results show that product quality and employee performance jointly influence the Customer Satisfaction variable. The results of the hypothesis test show that the T test value on X1 is 34.391 with a significance of 0.000 on .9% indicates that most of Customer Satisfaction is influenced by product quality (X1) and employee performance (X2), while the remaining 7.1% is due to other factors not covered in this research.